ANALISIS SEMIOLOGI ROLAND BARTHES PADA TERM ZAHRAH DALAM AL-QUR'AN - Haiva Satriana Zahrah (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This article contains an explanation regarding the meaning of the za?rah through interpretation from classical to contemporary times. Recently, a quite ambiguous understanding has appeared regarding women who are identified with flowers because they have a beautiful face, with a match in the pronunciation in the Al-Qur'an that mentions this. By using Roland Barthes' semiological theory in reading myths, one identifies a sign that is interpreted to give birth to various meanings. Therefore, the purpose of this study is to analyze the pronunciation of za?rah in the Qur'an by looking at its diachronic meaning through various interpretations of mufassir from classical to contemporary times based on Barthes' semilogy theory. This research is a literature study (library research) with a qualitative research type. The result of this research is that Barthes develops de Saussure's theory at the level/system II stage (second order signifying system), which is called connotation, with the ERC (expression, relation, content) pattern. Diachronically, the muafassir (Al-Thabarî, Al-Farrâ, Al-Zamakhsyarî, Al-Qurthubî, Al-Zuhaylî, and Qurasih Shihab) interpret za?rah with almost the same understanding in terms of the interpretations of the term za?rah over time, agreeing to understand the meaning of za?rah as jewelry plus other meanings. Meanwhile, Ibn Katsîr understands this meaning textually as a flower. Understanding the Qur'an both textually and contextually has something in common, namely za?rah as beauty